Distant metastasis in oral squamous cell carcinoma: Does the neutrophil-to-lymphocyte ratio act as a surrogate of the host immune status?. (January 2022) - Zanoni, Daniella Karassawa; Valero, Cristina; McGill, Marlena R.; Montero, Pablo H.; Shah, Jatin P.; Wong, Richard J.; Ganly, Ian; Patel, Snehal G.
Highlights: 1369 patients with oral cavity cancer operated between 1998 and 2015 were studied. Number of metastatic nodes and extranodal extension predicted distant failure. Neutrophil-to-lymphocyte ratio was an independent predictor of distant metastasis. Tumor and host factors should be considered when assessing distant metastasis risk. Abstract: Objectives: Distant metastasis (DM) is an important prognostic factor for oral squamous cell carcinoma (OSCC). The aim of this study is to evaluate the influence of host and tumor factors in development of DM. Materials and Methods: After IRB approval, 1369 patients with OSCC undergoing primary surgery were eligible for the study. The primary endpoint was the development of distant metastasis (DM). Patients were pathologically staged according to the American Joint Committee on Cancer, 8th Edition. Pre-operative peripheral blood counts were used to calculate neutrophil-to-lymphocyte ratio (NLR). Results: Median follow-up was 39 months (range 1–221). DM were identified in 126 patients during follow-up. When analyzed as a time-dependent covariate, neck recurrence (NR) was a significant predictor of DM (HR 16.35, 95% CI: 11.39–23.47, p < 0.001). NLR, margin status, vascular invasion, perineural invasion (PNI), grade, pT, number of metastatic lymph nodes, level IV involvement, and extra nodal-extension (ENE) were also significant. In multivariable analysis, NLR, margins, PNI, number of metastatic lymph nodes, and ENE maintained independent predictive capacity. Patients with NLR ≥ 5.7 were 3 times more likely to develop DM compared to NLR ≤ 2.9 (95% CI: 1.74–5.59, p < 0.001), patients with ≥ 5 metastatic lymph nodes were 2 times more likely to develop DM (95% CI: 1.18–3.60, p = 0.011), and those with ENE were 4 times more likely (95% CI: 2.67–8.20, p < 0.001) when compared to pNx/pN0 patients. Conclusions: NLR, number of metastatic lymph nodes, and ENE were the strongest independent predictors of DM in OSCC treated with primary surgery and appropriate adjuvant therapy.